The Effect of Health Education on the Level of Knowledge and Behavior in Diabetes Mellitus Management (Indian Journal of Public Health Research & Development, 2021)
Diabetes mellitus is a metabolic disease characterized by glucose levels in the blood that are more thannormal or hyperglycemia, this is due to a decrease in the body’s ability to react with insulin, or it could beimpaired insulin secretion.Riskesdas 2013 shows that diabetes mellitus sufferers in Indonesia are around6.9% or around 12 million people with 1.4% of diabetes sufferers in South Kalimantan or around 38,113people diagnosed with diabetes mellitus, especially type 2 diabetes mellitus which is related to lifestyle.Oneof the efforts made is health education. This research is an experimental research using pre-experimentalmethod with one group pretest-postest design. The sampling technique used consecutive sampling of 50people.The results of the effect of health education on the behavior of diabetes mellitus sufferers obtainedp-value = 0.0110.05, this indicates that Ho is accepted, which means that there is no effect of health education on increasingknowledge of diabetes mellitus sufferers in handling diabetes mellitus. These results were obtained fromthe pre and post-test scores of the respondents which indicated that there was an influence before and afterhealth education to the public.
Keywords: Diabetes Mellitus, Health Education, Knowledge, Behavior